In vivo elicitation is efficient in increasing essential oil yield with high anti-inflammatory sesquiterpene content in Varronia curassavica Jacq. - Melo, Elisa Ramos (2023)
Essential oils in plants are produced in very low concentrations and elicitation stands out among the techniques used to increase their productivity. This work evaluated the potential elicitor of salicylic acid (SA) or seaweed extract (SE) on the biomass yield, physiological parameters and essential oil production in Varronia curassavica Jacq. plants. The elicitors were applied through foliar spray in four serial applications (21, 34, 53 and 70 d after transplanting the seedlings to the pots - DAT), in concentrations of 1 mM (SA) and 5 mL L-1 (SE). The control plants were sprayed with water. Biometric measurements of plant height and number of branches were performed after 2, 3 and 4 elicitor applications. Plants were harvested at 91 DAT and biometric, biochemical and phytochemical parameters were evaluated. Application of SA resulted in increases in number of leaves (11.68%) and foliar concentrations of chlorophylls (57.67%), anthocyanins (73.80%), carotenoids (42.58%), total soluble sugars (19.48%) and essential oil (18%). The plants treated with SE had no changes in leaf biomass or essential oil production. The SA treatment increased by twice the amount of a-humulene and (E)-caryophyllene present in the essential oil while for SE treatment there was an average increase of 78.6%. It was concluded that the elicitation of V. curassavica plants by SA foliar pulverization is an efficient strategy for promoting the higher productivity of leaves and essential oil. Foliar pulverization of SA or SE modifies essential oil quality, inducing increases in the compounds of greatest interest for the pharmaceutical industry.